Triazole-conjugated spiropyran: synthesis, selectivity toward Cu(II), and binding study. Issue 44 (28th October 2015) - Kim, Inwon; Jeong, Dong-Cheol; Lee, Minhe; Khaleel, Zinah Hilal; Satheeshkumar, Chinnadurai; Song, Changsik
Graphical abstract: Highlights: Easy experimental procedures. Cheap chemicals were used to obtain the selective Cu(II) sensor. Naked eye detection. Without external stimuli Cu(II) selectively sensed through spiropyran to merocyanine open form. Abstract: Triazole-conjugated spiropyran was synthesized by Cu(I)-catalyzed azide–alkyne cycloaddition and its metal sensing properties were investigated. Color changes were observed upon the formation of metal complex between the spiropyran and Cu 2+, which was found to be selective for Cu 2+ ions among Co 2+, Hg 2+, Li +, Mg 2+, Ni 2+, Zn 2+, Cd 2+, and Cu 2+ ions. Moreover, because of the color change, the complex could be detected by the naked eye. An interesting two-stage metal binding mechanism was observed for the sensing process. First, a metal cation brought the two 1, 2, 3-triazoles together. Second, the Cu 2+ ion was selectively sensed by the conversion of the spiropyran to the merocyanine form.